2017
DOI: 10.3390/su9040603
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Sustainability Assessment of Public Rental Housing Community Based on a Hybrid Method of AHP-Entropy Weight and Cloud Model

Abstract: As an essential part of a city, community is significant to the sustainable development of the city. At present, research on community sustainability assessment systems is relatively scarce. The existing community sustainability assessment systems often lack integrated consideration of community sustainability. For example, these systems especially place emphasis on the ecological and environmental aspects, but the economic and social aspects of sustainability are partially ignored. In order to comprehensively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(10 citation statements)
references
References 72 publications
(114 reference statements)
0
10
0
Order By: Relevance
“…The concept of entropy is derived from the principle of thermodynamics handling energy, and later introduced information theory by Shannon [28]. The EM method uses the value of information entropy to calculate the weights of evaluation indices [29]. It is worth noting that the difference coefficient is the key in the process of calculating the weights, because the difference coefficient and the weight of the index are proportional.…”
Section: Calculation Of the Objective Weights Of Evaluation Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of entropy is derived from the principle of thermodynamics handling energy, and later introduced information theory by Shannon [28]. The EM method uses the value of information entropy to calculate the weights of evaluation indices [29]. It is worth noting that the difference coefficient is the key in the process of calculating the weights, because the difference coefficient and the weight of the index are proportional.…”
Section: Calculation Of the Objective Weights Of Evaluation Indicesmentioning
confidence: 99%
“…The AHP with three scales (-1, 1) is first used to obtain the subjective weights of the evaluation indices, and then the objective weights of the evaluation indices determined by the EM are applied to revise the result calculated by the AHP with three scales (-1, 1). Finally, according to [29], Equation 18 is applied to calculate the weights of the evaluation indices as follows.…”
Section: Calculation Of the Weights Of Evaluation Indicesmentioning
confidence: 99%
“…In the process of assessing the bidder's unit prices, the greater the difference between engineer's estimate price and the unit price from the bidder's offer, the greater the likelihood that the line item will be unbalanced, and information entropy may just show this difference. Information entropy is defined as (Lan, Yang, & Huang, 2017;Shemshadi, Shirazi, Toreihi, & Tarokh, 2011;Wu, Duan, Zuo, Zhao, & Tang, 2017)…”
Section: Determination Of the Weights Of Line Itemsmentioning
confidence: 99%
“…The earliest application of the entropy weighting method in conjunction with AHP was a study of ship investment decision making [29]. Nowadays, the AHP-entropy method has been known and used in the assessment of various industries, including the safety assessment of food-waste feed [27], the safety evaluation of smart grids [30], the risk assessment in banks [31], and in community sustainability assessments [32]. These studies demonstrated that this integrated method is scientific and effective.…”
Section: Weight Assignmentmentioning
confidence: 99%